Polypectomy techniques among gastroenterologists in Norway – a nationwide survey - Pedersen, Ina B.; Løberg, Magnus; Hoff, Geir; Kalager, Mette; Bretthauer, Michael; Holme, Øyvind (Endoscopy International Open, 2018)
Background and study aims Incomplete polyp removal has been estimated to cause 27 % of all colorectal cancers detected soon after colonoscopy. There is limited information regarding polypectomy techniques among endoscopists. The article is a nationwide survey of polypectomy techniques among Norwegian endoscopists.Materials and methods We invited all board-certified gastroenterologists in Norway to complete a web-based questionnaire about their polypectomy technique. Inadequate polypectomy techniques were defined as using biopsy forceps for polyps larger than 3 mm in diameter, using hot biopsy forceps for polypectomy, and using the same electrocautery output irrespective of polyp size and morphology. Results Twenty-six of 30 Norwegian gastroenterology departments participated in the study. A total of 119 endoscopists received the survey, and 70 (59 %) responded. Mean duration of endoscopy practice was 11.5 years, and 95 % had performed more than 1,000 colonoscopies during their career. Twenty-eight endoscopists (40 %) used one or more inadequate polypectomy techniques: 10 (14.3 %) used biopsy forceps for removal of polyps larger than 3 mm in diameter, five (7.1 %) used hot biopsy for polypectomy, and 17 (24 %) used the same electrocautery output for all polypectomies. Five (7 %) endoscopists reported that they did not remove polyps smaller than 4 mm.Conclusion A substantial number of Norwegian endoscopists use inadequate polypectomy techniques. Improved training and certification of endoscopists is warranted.